Preparation and Characterization of Carvedilol Solid Dispersion by Kneading Method - Ali Q. Hatem; Wedad K. Ali (College of Pharmacy / Mustansiriyah University, 2023)
Solid dispersion using hydrophilic carrier is one of the approaches that has a potential to increase solubility, dissolution rate and consequently the oral bioavailability of poorly-water soluble drugs. In this study, class II drug "Carvedilol" (CVD) was used because of its poor solubility, it serves as a model drug that contributes to irregular dissolution and limited bioavailability. CVD: PVP K30 solid dispersion formulations SD1, SD2 and SD3 were prepared by kneading method at different weight ratios ,1:1; 1:2 and 1:4 respectively and evaluated for drug content, solubility and dissolution rate. Kneading method enhances the stability of drugs and suitable for processing thermolabile substances. The optimum solid dispersion ratio was characterized also for drug-carrier interaction by FTIR spectroscopy, and crystallinity by SEM and PXRD and compared with physical mixture and pure drug powder. The results showed that the solubility of carvedilol increased by increasing the proportion of PVP K30 used in the dispersion of the drug. On the other hand, dissolution study revealed a significant enhancement in the dissolution rate of the drug using solid dispersion compared to pure drug and physical mixture. X-ray diffraction of the solid dispersion suggest that the drug's transformation from crystalline to amorphous form may be responsible for the observed improvement in dissolving rate. The carvedilol solid dispersion improved the solubility and dissolution, which depend on the carrier concentration ratio. The dissolution of drugs increased with an increase in carrier content. The studies of PXRD, SEM, and FTIR revealed the amorphous nature of the drug in solid dispersion. The solid dispersion by kneading approach using PVP K30 as a carrier is a potential method for improving CVD's solubility and dissolution rate.